Cross-sectional review of the response and treatment uptake from the NHS Health Checks programme in Stoke on Trent - Cochrane, Thomas (Oxford University Press, 2013)
BACKGROUND: As part of national policy to manage the increasing burden of chronic diseases, the Department of Health in England has launched the NHS Health Checks programme, which aims to reduce the burden of the major vascular diseases on the health service. METHODS: A cross-sectional review of response, attendance and treatment uptake over the first year of the programme in Stoke on Trent was carried out. Patients aged between 32 and 74 years and estimated to be at ≥20% risk of developing cardiovascular disease were identified from electronic medical records. Multi-level regression modelling was used to evaluate the influence of individual- and practice-level factors on health check outcomes. RESULTS: Overall 63.3% of patients responded, 43.7% attended and 29.8% took up a treatment following their health check invitation. The response was higher for older age and more affluent areas; attendance and treatment uptake were higher for males and older age. Variance between practices was significant (P < 0.001) for response (13.4%), attendance (12.7%) and uptake (23%). CONCLUSIONS: The attendance rate of 43.7% following invitation to a health check was considerably lower than the benchmark of 75%. The lack of public interest and the prevalence of significant comorbidity are challenges to this national policy innovation.